If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 24 = 24 + -1y Reorder the terms: 24 + x = 24 + -1y Add '-24' to each side of the equation. 24 + -24 + x = 24 + -24 + -1y Combine like terms: 24 + -24 = 0 0 + x = 24 + -24 + -1y x = 24 + -24 + -1y Combine like terms: 24 + -24 = 0 x = 0 + -1y x = -1y Solving x = -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = -1y
| 12y^2-19y-21=0 | | x^4+4x=-c | | x^4+4x=c | | 4x+1+4c=5c-3x+6 | | 6y^2+23y+7=0 | | 3y^2-11y+10=0 | | 5x-8+3(2X-5)= | | 4y^2+9y+5=0 | | -2(x+3)=-2(x+5)-4 | | -2(x+3)=-2(x+2)-4 | | 2y^2+5y-12=0 | | 6y^2+5y-4=0 | | 8y^2+10y-3=0 | | 12y^2-17y+6=0 | | 3x^2=2+5x | | 3a+2=2a+5 | | 4y^2-3y-1=0 | | 4=12-2x | | 5y^2+11y-12=0 | | x+10+-24=0 | | 3y^2-5y-12=0 | | 5y^2+4y-1=0 | | (8x^2-5x^3)-(2x^2-9x^3)= | | (5x-8)(3x+9)= | | 3a=1-6c | | 3a+6c=1 | | y^2+16y+13=0 | | x-4=6x-15 | | [x+10(27-x)]+[10x+27-x]=9 | | 16a-4=6a-34 | | 8x-3(3x+4)=11 | | x^2+x-15=0 |